Bioavailability of Different Zinc Sources in Pigs 0–3 Weeks Post-Weaning - Tina S. Nielsen; Maiken N. Engelsmann; Sally V. Hansen; Hanne Maribo (Animals, 2022)
The bioavailability of dietary zinc (Zn) in pigs may differ according to the Zn source and is affected by other components in the diet. The aim was to determine the biomarkers of Zn bioavailability (apparent total tract digestibility of Zn and serum Zn status) following six different sources of added Zn and their effect on the performance and faecal consistency score in piglets 0–3 weeks after weaning on day 28. The sources of Zn were Zn oxide (ZnO), Zn sulfate (ZnSO4), porous ZnO, Zn-glycinate, amino acid-bound Zn and hydroxy covalent-bound Zn added at 100 mg/kg (ZnO and ZnSO4 also added at 1000 mg/kg), in a total of eight treatments (n = 12/treatment). Pigs were individually housed, and titanium dioxide was included as an indigestible marker in the feed. The digestibility of Zn on day 14 post-weaning was negative for all six Zn sources at 100 mg Zn/kg, indicating insufficient Zn supply. The digestibility of Zn differed according to the Zn source, but the digestibility of Zn from ZnO and ZnSO4 did not differ between processed inorganic or chelated organic sources of Zn. However, the differences in Zn digestibility between Zn sources were not reflected as differences in the serum Zn status, feed intake, gain or probability of diarrhoea.